THE EFFECT OF TEMPERATURE ON THE CONDUCTIVITY OF POLYMER FILMS - Susilawati Susilawati (Postgraduate, University of Mataram, 2018)
The effects of temperature on PVA (Poly Vinyl Alcohol) based organic blends containing chlorine have been studied for their potential applications in electrochemical devices. The composite polymers PVA-Chloral Hydrate (CH) blends were blended separately with 23, 34, 45 and 57% CH. The composite films were prepared by solvent-casting method and each film has been heated different temperature up to 353 K. The electrical properties have been studied using LCR meter and impedance analyzer in the frequency range from 20 Hz to 1 MHz. The conductivity-temperature relation study revealed that an increase conductivity of the PVA-CH blends with increasing temperature up to 353 K. The increase of conductivity with temperature is attributed to the increase of free ion mobility due to thermal energy kT and possible more ions gained kinetic energy via the thermally activated hopping of charge carriers between trapping sites and phonon-assisted quantum tunneling through a barrier separating two equilibrium positions. The conductivity activation energy obtained decreases with the blend composition increases.Keywords: Influence, Temperature, Conductivity, Polymer Films